Collective memories, place-framing and the politics of imaginary futures in sustainability transitions and transformation. Issue 138 (January 2023) - Feola, Giuseppe; Goodman, Michael K.; Suzunaga, Jaime; Soler, Jenny
Abstract: A geographical perspective is crucial to understanding sustainability transitions and transformation, but previous research on place framing in sustainability transitions and transformation has had a marked focus on the politics of the future and its performativity in the present. This paper analyzes place-framing in sustainability transitions and transformation by examining how the conflicting collective memories of a place and the framings of the future of this place interact and lead to the justification of particular forms of socio-material development, land use and sustainability of the peri-urban spaces of the city of Sogamoso, Colombia. Based on 38 semi-structured interviews, we identify three distinct assemblages of future visions, collective memories and place frames, which we call urban development, recovering tradition, and cultural revitalization. The analysis shows that place framing is an exercise through which collective memories and future visions are connected and co-constituted in a spatio-temporal 'dialogue': collective memories, future visions and place frames are processes of social construction activated in the attempt to shape or contest sustainability transitions and transformation. We contend that the existence and mobilization of collective memories—and their critical influence on future visions—are a core aspect of the politics of place framing fundamental to the socio-material processes of sustainability transitions and transformation. Furthermore, a politics of place-making in sustainability transitions and transformation involves acknowledging and negotiating collective memories of the past as much as future visions. This suggests ways to critically counterbalance the marked future orientation taken in recent years by sustainability science and transition studies.